Menganalisis Lingkungan Eksternal Organisasi (Menganalisis SWOT) - Kusumaningrum, Hesti; Wijayanti, Rahma; Khusniyah, Difa (Cendekia : Jurnal Pendidikan dan Keagamaan, 2024)
The success and sustainability of an organization, including a company, is greatly influenced by an analysis of its environment. The outside world includes many things, such as economic, technological, social, political, and environmental circumstances, and can provide opportunities or present threats to the company. Descriptive methods are used in this research to analyze the external environment of a company, especially in terms of industry, economic conditions, and social conditions. This research technique also involves scanning, monitoring, gathering competitive intelligence, and analyzing strengths, weaknesses, opportunities, and threats (SWOT). A company can make plans to handle difficulties and capitalize on opportunities by understanding the external environment.